Tata Cara Penyitaan Dan Pelelangan Serta Perlindungan Barang Milik Wajib Pajak - Komang Edy Dharma Saputra (Universitas Mahendradatta, 2019)
Development of taxation should be increased, if not fostered community members resulted inthe taxpayer less responsible and less participate in bearing the burden of the state and in maintainingthe continuity of the national development program. To further enhance the role of the taxpayer inreceipt of state sector of taxes necessary to have a law reform national tax, with the aim of furtherconfirm the independence of the nation to finance national development with the road more on the bestof our ability through increased state revenue through taxation, simplifying the tax system that includesthe type tax, tax calculation of tax payment and tax records, fix the taxation apparatus both concerningthe work procedures, work discipline and mental tax officials, tax burden more fair and reasonable, sothat on the one hand to encourage taxpayers consciousness paying taxes and on the other hand shallThe new tax increases. Law - Tax Law has encountered several improvements and is currently in useAct 16 of 2009 which is to amend Law No. 6 of 1983. Law No.36 of 2008 is an amendment to Law No.7 of 1983 on Income Tax, and Law 42 of 2009 is the change in the Act 8 of 1983 on Value Added Taxand the Goods and Services Sales Tax on luxury goods. In practice, if done auction, items auctionedprice could be lower than the normal price. This could result in losses for taxpayers because the nutrientobject sold at below market prices. Moreover, a thing that is impossible to do by the taxpayer is toreclaim the goods that have been auctioned off, because it belongs to the auction winner based on theminutes of the auction. For that we need a legal protection for the taxpayer / undertaking Taxes on theimplementation of the seizure and auction. Taxpayer / Tax Insurers have the right remedy for the implementation of seizure and auction in question.